Synthesis of implantable ceramic coatings and their properties - Topuz, Mehmet; Yigit, Oktay; Kaseem, Mosab; Dikici, Burak (Elsevier, 2023)
Nowadays, emphasis on metallic materials, coating materials, and coating technology to improve osseointegration and increase the lifespan of biological fixation prostheses has become a topic of great interest in the field of prosthetic research. Many published studies showed that the bioactivity-coated surfaces increase the implant–tissue compatibility with their similarities to the bone structure. Therefore several coatings are widely used to increase osteoconductivity on implant material surfaces in the biomedical industry. In this section, synthesis techniques, mechanical and corrosion behavior, osseointegration, and esthetic responses of implantable ceramic coatings, especially considering the last published reports, are reviewed in detail. Besides, an answer to the “are the coatings suitable for in vivo conditions?” is investigated. © 2023 Elsevier Ltd. All rights reserved.
Keywords: Bioceramic coating; corrosion behavior; implantable coating; mechanical properties; osseointegration; surface modification